Sistem Penjadwalan di PT. XYZ - Fernaldi Darmasaputra Leksono; I Gede Agus Widyadana (Jurnal Titra, 2015)
Production scheduling in a manufacturing company is an important point to control the production process movements. PT. XYZ doesn’t have a scheduling system which fit for their daily production process. This research intends to make a production scheduling system which fit for PT. XYZ. Production scheduling is useful for minimizing delays in delivery as a result of delays in the production process. Scheduling method used in this study is earliest due date method. Earliest due date method is chosen in aim to minimize the maximum tardiness which happened in a project. Scheduling system was made starting from the making of the schedule up to controlling process of the schedule.